2015
DOI: 10.1155/2015/923857
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Late-Onset Bleb-Related Endophthalmitis Treated with Pars Plana Vitrectomy

Abstract: Purpose. To investigate clinical results on bleb-related endophthalmitis (BRE) after trabeculectomy treated with pars plana vitrectomy (PPV) and to evaluate influence factors for visual prognosis. Methods. Investigating medical records retrospectively, BRE was defined as an endophthalmitis induced by bleb infection. A total of 2018 eyes of 1225 patients who had trabeculectomy between December 2000 and July 2013 were included in this study. Eleven eyes of 11 patients with BRE were performed with PPV. Results. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 22 publications
(39 reference statements)
0
13
1
Order By: Relevance
“…The results of this study showed that BAE is one of the common forms of infectious endophthalmitis. In previous studies, the mean period from initial trabeculectomy to bleb-related infection was from 1 to 16 years [7]. In our study, BAE develops earlier than previous reports.…”
Section: Discussioncontrasting
confidence: 39%
“…The results of this study showed that BAE is one of the common forms of infectious endophthalmitis. In previous studies, the mean period from initial trabeculectomy to bleb-related infection was from 1 to 16 years [7]. In our study, BAE develops earlier than previous reports.…”
Section: Discussioncontrasting
confidence: 39%
“…Our study demonstrated a high rate of poor visual outcomes even with aggressive and prompt antibiotic treatment, which is congruent with previous reports. 1,[3][4][5]8,[11][12][13] In our cohort of 36 eyes, 86% of eyes were blind with vision less than 20/200, and 80% with less than 20/400 at resolution of infection. The longterm visual outcomes were very limited in this cohort of patients, but the 6-month follow-up data mirrored those at the time of infection resolution, with an average vision of HM.…”
Section: Discussionmentioning
confidence: 99%
“…1,4 Intravitreal antibiotics with or without pars plana vitrectomy (PPV) are the mainstay of treatment. 1,4,5 Visual prognosis despite prompt treatment is guarded, with endophthalmitis patients often having both poor visual outcomes and intraocular pressure (IOP) control. 6 In this study, we describe the demographics, risk factors, presenting signs, diagnostic workup, treatment, complications, and visual outcomes of eyes with BRE at a US tertiary care facility over a 15-year period.…”
Section: Introductionmentioning
confidence: 99%
“…Potentially dangerous intraoperative and postoperative complications may occur at a frequency that cannot be ignored, including surgery-related bleb scarring, hypotony, bleb leak, and bleb infection, which are associated with a high rate of additional surgeries. [2][3][4] Although cataract extraction can deepen a crowded anterior chamber, the adhered angle can still remain. [5][6][7] Combined with goniosynechialysis (GSL), phacoemulsi cation and intraocular lens (IOL) implantation may still fail to achieve a satisfying IOP level resulted from the disabled trabecular meshwork (TM) [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%